The effects of lactic acid bacteria and molasses on microbial community and fermentation performance of mixed silage of king grass and cassava foliage - Liu, Yue; Chen, Ting; Sun, Rong; Zi, Xuejuan; Li, Mao (Frontiers in Animal Science, 2022)
In the present study, we aimed to investigate the effects of lactic acid bacteria (LAB) and molasses (M) on microbial community and fermentation performance of mixed silage of king grass (KG) and cassava foliage (CF). A completely randomized design was used for the experiment. Mixed material was ensiled with no additive added (CK) for 60 days. Alternatively, mixed silage was supplemented with M, LAB (L), or M + LAB (ML) and then subjected to fermentation. Compared with the CK group, the contents of lactic acid and propionic acid in the L group were enhanced while the content of acetic acid was reduced. Moreover, the levels of pH, butyric acid, and ammonia-N were not significantly changed. In contrast, the lower contents of pH, acetic acid, propionic acid, and butyric acid, ammonia-N in the M and ML groups were observed, while the content of lactic acid was elevated. Additives could change the silage quality of mixed silage to different extents. The effect of the L treatment was not ideal, and the ML group had a better fermentation quality compared with the M group. In terms of microbial community, the relative abundance of desirable Lactobacillus was increased in the M, L, and ML groups. The relative abundance of Pseudomonas was decreased in the M and L groups. Compared with the CK group, the relative abundance of Stenotrophomonas was decreased, especially in the M (0.18%) and ML (0.19%) groups. For Paenibacillus, its relative abundance was increased in the ML group and more significantly increased in the M group. In summary, the combination of LAB and M at an equal ratio had a more positive effect on the fermentation quality and microbial community of mixed silage than LAB and M alone.